State Examination as a Way to Assess Postgraduate Students’ Teaching Competencies - B. I. Bednyi; K. D. Dyatlova; N. V. Rybakov (Высшее образование в России)
The article discusses the system for developing and assessing teaching competencies of PhD program graduates. The experience of Russian universities in conducting the final state examination in postgraduate schools is considered. The authors analyze the options for the distribution of the competencies being assessed between the two parts of the final state certification of postgraduate students: the state examination and the defense of their research report. The system developed and implemented at Lobachevsky University for postgraduate students’ step-by-step training for a teaching career at a higher education institution is discussed in detail, including: 1) theoretical training in the framework of the discipline “Psychology and Pedagogy of Higher Education”, 2) teaching practice, 3) preparation of a study manual based on the results of the postgraduate student’s dissertation research, and its defense at the final state examination. Assessments of the practice-oriented format of the state examination by postgraduate students are presented.